Perempuan dalam Erotisme Seni Murni - nunung nurdjati (EKSPRESI, 2009)
Women in Fine Art Eroticism. For the writer, pornography and eroticism in art are two very difference issues depending on the artists driving force and viewpoint. Painting is a personal expression that does not have to be associated with any interest. Exhibition is an effort to communicate the works of art to the public. In the event, the art devotees comprehend, evaluate, and relish them. A problem arises when some people regard erotic paintings as pornographic, valueless paintings whereas some others consider them acceptable works of art. The different opinion is caused by the quality of each individual perception. How somebody judges an art piece is very much rests on his thinking framework. Human perception is influenced by the accumulation of shape perception that believed to be mental attitude of each individual Keywords: Pornography, erotism, painting, personal expression.